Dziennik - Lechon, Jan, 1899-1956.; Loth, Roman (Warszawa : Panstwowy Instytut Wydawniczy, 1992)
The diary of a famous Polish poet, a member of the Skamander group, who lived in New York City from 1941 until his death in 1956.
t. 1. 30 sierpnia 1949-31 grudnia 1950 -- t. 2. 1 stycznia 1951-31 grudnia 1952 -- t. 3. 1 stycznia 1953-30 maja 1956.
Keywords: Lechon, Jan, -- 1899-1956 -- Diaries; Poets, Polish -- 20th century -- Diaries; Authors, Polish -- 20th century -- Diaries